Activity of Thioallyl Compounds From Garlic Against Giardia duodenalis Trophozoites and in Experimental Giardiasis - Argüello-García, Raúl; de la Vega-Arnaud, Mariana; Loredo-Rodríguez, Iraís J.; Mejía-Corona, Adriana M.; Melgarejo-Trejo, Elizabeth; Espinoza-Contreras, Eulogia A.; Fonseca-Liñán, Rocío; González-Robles, Arturo; Pérez-Hernández, Nury; Ortega-Pierres, M. Guadalupe (Frontiers in Cellular and Infection Microbiology, 2018)
Fresh aqueous extracts (AGEs) and several thioallyl compounds (TACs) from garlic have an important antimicrobial activity that likely involves their interaction with exposed thiol groups at single aminoacids or target proteins. Since these groups are present in Giardia duodenalis trophozoites, in this work we evaluated the anti-giardial activity of AGE and several garlic's TACs. In vitro susceptibility assays showed that AGE affected trophozoite viability initially by a mechanism impairing cell integrity and oxidoreductase activities while diesterase activities were abrogated at higher AGE concentrations. The giardicidal activities of seven TACs were related to the molecular descriptor HOMO (Highest Occupied Molecular Orbital) energy and with their capacity to modify the –SH groups exposed in giardial proteins. Interestingly, the activity of several cysteine proteases in trophozoite lysates was inhibited by representative TACs as well as the cytopathic effect of the virulence factor giardipain-1. Of these, allicin showed the highest anti-giardial activity, the lower HOMO value, the highest thiol-modifying activity and the greatest inhibition of cysteine proteases. Allicin had a cytolytic mechanism in trophozoites with subsequent impairment of diesterase and oxidoreductase activities in a similar way to AGE. In addition, by electron microscopy a marked destruction of plasma membrane and endomembranes was observed in allicin-treated trophozoites while cytoskeletal elements were not affected. In further flow cytometry analyses pro-apoptotic effects of allicin concomitant to partial cell cycle arrest at G2 phase with the absence of oxidative stress were observed. In experimental infections of gerbils, the intragastric administration of AGE or allicin decreased parasite numbers and eliminated trophozoites in experimentally infected animals, respectively. These data suggest a potential use of TACs from garlic against G. duodenalis and in the treatment of giardiasis along with their additional benefits in the host's health.